Can a Mood Tracker Improve Young People's Mental Health? - Kaneko, Izumi (Faculty of Medicine, Diponegoro University, 2023)
Background: Today, mental health is a major concern among all age groups. Japan is the only country among G7 countries where suicide is the largest cause of death among youths 10-19 years old. However, many people find it difficult to confide in others about private mental health issues. Objective: We pilot-tested a “Mood Tracker” tool intended to help users record, reflect upon, and exercise control over their own emotions, in order to assess its acceptability and to explore its impact among Japanese university students.Methods: Participants were 20 medical students recruited at Fukushima Medical University. They were given a calendar and a paper listing 16 different emotions, with instructions to designate a different color for each emotion on the list, and to color each day of a month according to that day’s overall emotion. In addition, participants filled out a questionnaire before, right after, and a month after mood tracking, for self-assessment of mental state and satisfaction with the tool. Results: All participants except for one completed the intervention and provided positive comments. Although not statistically significant, the proportion of students who were highly satisfied with their school life increased from 25% before the intervention to 42% one month after the intervention. Conclusion: This small-scale pilot test suggested that mood tracking was well accepted among Japanese medical students and worth further investigation for its potential to positively impact mental health.